2021
DOI: 10.1021/acsestengg.1c00120
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Gas–Water Interface to Enhance Photocatalytic Degradation of Volatile Organic Compounds

Abstract: The gas–water interface plays an important role in the photocatalytic degradation of volatile organic compounds (VOCs). Herein, a novel photocatalytic reactor with a tunable gas–water interface was designed and utilized to investigate the performance of photocatalytic degradation of VOCs. The relationship between the key operating parameters of the reactor and VOCs mineralization was investigated in detail with toluene as a model pollutant. The results showed that a tunable gas–water interface was formed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…[22,23] Among these factors, many authors have focused on the effect of relative humidity (RH) on the photocatalytic degradation of gaseous VOCs. [24] The influence of water on the kinetics of photocatalytic degradation and the lifetime of the catalyst is still up for debate. In real-world applications, it was discovered that a high concentration of water vapour in the feed stream had a negative impact on the removal efficiency of VOCs from the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Among these factors, many authors have focused on the effect of relative humidity (RH) on the photocatalytic degradation of gaseous VOCs. [24] The influence of water on the kinetics of photocatalytic degradation and the lifetime of the catalyst is still up for debate. In real-world applications, it was discovered that a high concentration of water vapour in the feed stream had a negative impact on the removal efficiency of VOCs from the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Low concentrations of oxygen and water cannot produce enough ROSs, which lead to incomplete degradation of VOCs, thus forming carbonaceous intermediates deposited at the active site of the catalyst, leading to deactivation of the catalyst, 7 while higher concentrations can cause competitive adsorption with the pollutant molecule. 8 It reported that surface lattice oxygen in transition metal oxides involved redox reactions and behaved as a significant ROS and plays a crucial role in traditional VOC combustion though a series of reaction steps. 9,10 Especially, surface lattice oxygen also serves as a redox site for activation of molecular oxygen and promotes ring opening of aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, this behavior is limited by the concentration of molecular oxygen and molecular water. Low concentrations of oxygen and water cannot produce enough ROSs, which lead to incomplete degradation of VOCs, thus forming carbonaceous intermediates deposited at the active site of the catalyst, leading to deactivation of the catalyst, while higher concentrations can cause competitive adsorption with the pollutant molecule …”
Section: Introductionmentioning
confidence: 99%
“…The expansion of the world’s population and unrestrained industrial growth in the past few decades have escalated the consumption of fossil fuels (coal, petroleum, natural gas), as well as the unabated release of greenhouse gas (CO 2 ). According to a report from Earth System Research Laboratories, the CO 2 content in the atmosphere in 2019 was much beyond preindustrial levels, which has intensified global warming and caused anomalous climate change. Meanwhile, a vast number of environmentally harmful pollutants and toxins (NO x , SO x , organic pollutants) arising from fossil fuel combustion are discharged into the air and water bodies, posing a danger to the ecosystem and contributing to pollution-related diseases. To ensure global sustainability, developing environmentally benign and energy-efficient technologies to decrease the CO 2 concentration and eliminate environmental pollutants should therefore be our goal.…”
Section: Introductionmentioning
confidence: 99%